Provision and management of health facilities and services in primary schools: a pre-requisite for effective universal basic education in Nigeria (2010)
Basic education provides a foundation for acquisition of further knowledge, skills, attitudes and competencies in future endeavour. It is particularly crucial in Nigeria as it may be the only opportunity for many children to have access to formal education. The present Universal Basic Education (UBE) scheme was designed to cover Primary school and Junior Secondary School. The Primary school education is crucial to the success of UBE scheme. The paper examined primary school education and found that the provision of health facilities and services is grossly inadequate. Meanwhile, poor school health environment will produce unhealthy staff and pupils and such situation will invariably hamper the effectiveness of teaching and learning. Therefore, the paper suggested the strategies for the provision and management of health facilities and services in Nigerian Primary schools to enhance the effectiveness of UBE scheme.